MAGNETIC FIELD GENERATION BY BIERMANN BATTERY AND WEIBEL INSTABILITY IN LABORATORY SHOCK WAVES - Gregori, G; Miniati, F; Reville, B; Drake, R (2013)
Magnetic field generation in the Universe is still an open problem. Possible mechanisms involve the Weibel instability, due to anisotropic phase-space distributions, as well as the Biermann battery, due to misaligned density and temperature gradients. These mechanisms can be reproduced in scaled laboratory experiments. In this contribution we estimate the relative importance of these two processes and explore the laser-energy requirements for producing Weibel dominated shocks. © The Author(s) 2013.